PERLINDUNGAN HUKUM BAGI ANAK DI KOTA BONTANG PERSPEKTIF UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Raidon Hutahean (Law Department, University of Widya Gama Mahakam Samarinda, 2017)
The legally required position of children must be given protection and law enforcement for the offender who caused casualties in children is very important. Moreover, children had been seen in the family is not fully granted their rights as children. Even the legal facts indicate crimes against children mostly committed by those closest relatives among themselves as parents, other relatives, and the neighbourhood where he lived. Events on children in Bontang shows that Bontang Industrial city needs to be noticed by all people because they happen violence against children.